PENGARUH KOMIK DIGITAL DALAM MENINGKATKAN PENGUASAAN KONSEP DAN DAYA BERPIKIR KRITIS SISWA SEKOLAH DASAR - Rizkya Fitri Anisa; Atep Sujana; J. Julia (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2023)
This early learning media is really needed to support the achievement of learning goals by students at school. Learning media can allegedly be a forum for communication and equalization of perceptions of material between teachers and students. When Covid-19 occurred, teachers were required to develop innovations in learning, both learning models and learning media. Especially in learning media, during Covid-19, teachers were encouraged to be creative and innovate in making digital-based learning media. This is because digital learning media can make it easier for students at home to access it. Recently, the digital media that has been popularly used, especially during the pandemic, is digital-based comic visual learning media. Digital comics are a novelty from conventional comic forms which are usually found in the form of books or sheets of paper. Digital comics are designed with an attractive appearance and are equipped with relevant learning material content so that they are believed to be able to facilitate students' mastery of the material as best as possible, even though the learning is carried out virtually outside of school. The focus of the research was to determine the effect of using digital comics in an effort to improve the quality of learning outcomes in the form of mastery of a concept and critical thinking skills of phase C class V students in integrated learning of human digestion science and science. The research adopted an experimental research method by implementing a One-Group Pretest-Posttest design. The pretest and posttest were carried out with the aim of finding out whether there was an influence, even the size of the influence, of using comics in communicating the material being taught. The results of the research found that there was an influence of the use of digital comics in increasing the mastery of concepts and critical thinking skills of class V students using human digestion as material even though learning was carried out face-to-face in class